A Hybrid Cryptosystem Using Rprime RSA And Extended Tiny Encryption (XTEA) For Securing Message - Santoso, Zikri Akmal; Budiman, Mohammad Andri; Efendi, Syahril (Data Science: Journal of Computing and Applied Informatics, 2025)
Abstract. Ensuring the security of messages in sending message publicly is very important, we must ensure the security of messages with one of security method called cryptography. Focusing solely on security can affect the speed of message delivery processes. Therefore, this research is conducted to provide solutions to both of these issues. Thus, this research will discuss the Analysis of Hybrid Cryptography Scheme in the combination of RPrime RSA and XTEA (Extended Tiny Encryption) in securing instant messages. Hybrid cryptography is one of the methods in cryptography that allows to enhance speed of message delivery with messages encrypted by symmetric algorithms and the symmetric algorithm keys will be encrypted using asymmetric algorithms, public keys. RPrime RSA is an asymmetric public key algorithm and one variant of RSA, which is a combination of Rebalanced RSA and MPrime RSA algorithms. XTEA is a symmetric key algorithm and improved version of the TEA algorithm. This research tested by using strings with uppercase letter, numeric, and punctuation characters with the value of k in RPrime RSA from 2 to 6 with unconstrained modulus digits. The result of the test indicate that the required time for encryption and decryption is proportional, the time processing for factorization to get d is proportional to the value of k.